IMPLEMENTASI PROGRAM LAYANAN VOLUNTARY COUNSELING AND TESTING (VCT) HUMAN IMMUNODEFICIENCY VIRUS/ ACQUIRED IMMUNO DEFICIENCY SYNDROME (HIV/AIDS) DI PUSKESMAS SUMBERPUCUNG KABUPATEN MALANG - Maya Dinama; Supriyadi Supriyadi; Nurnaningsih Herya Ulfah (Preventia : The Indonesian Journal of Public Health, 2017)
Abstract :The incidence of HIV/AIDS in Malang Regency in 2008-2014 hasincreased prevalence. The distribution of HIV/AIDS cases in Malang Regency is based on the risk factor of heterosexual 74%, 13% injecting drug users, 4% homosexuals, 5% from mother, 0%, 0% bisexual, and 3% unknown. Sumberpucung Sub-District was ranked second highest with 79 new cases. One of the prevention efforts of HIV / AIDS is through the service Voluntary Counseling and Testing (VCT). The study aims to find out the implementation of HIV/AIDS VCT service program at Sumberpucung CHC of Malang Regency. This research is descriptive research using quantitative method. Variables in research are input, process andoutput. Determination of research subjects using non probability samplingtechnique. Data collection is done by direct observation and documentation. The instrument used is a checklist. Data analysis uses descriptive statistics to calculate mean, median, mode. Categorization is done on each subvariabel using Paretto theory. The result of the research of the input variable on the availability of human resources is less good, the availability of facilities is less good, the availability of infrastructure is good, and the availability of the forms is good. The results ofresearch on the process variables in pre-testing counseling are less good and post-testing counseling is less good. The results of the output variables on sustainable support services are less good.Key Words :Implementation, VCT Services, HIV/AIDSAbstrak: Angka kejadian HIV/AIDS di Kabupaten Malang pada tahun 2008-2014 mengalami peningkatan prevalensi. Distribusi kasus HIV/AIDS di Kabupaten Malang berdasarkan faktor resikonya yaitu heteroseksual 74%, pengguna narkoba suntik 13%, homoseksual 4%, tertular ibunya 5%, mantan TKW 0%, biseksual 1%, dan tidak diketahui penyebabnya 3%. Kecamatan Sumberpucung menempati urutan kedua tertinggi dengan 79 kasus baru. Salah satu upaya preventif penanganan HIV/AIDS adalah melalui layanan Voluntary Counselling and Testing (VCT). Penelitian bertujuan untuk mengetahui implementasi program layanan VCTHIV/AIDS di Puskesmas Sumberpucung Kabupaten Malang. Penelitian inimerupakan penelitian deskriptif menggunakan metode kuantitatif. Variabel dalam penelitian adalah input, proses dan output. Penentuan subyek penelitian menggunakan teknik non probability sampling. Pengumpulan data dilakukan dengan observasi langsung dan dokumentasi. Instrumen yang digunakan adalah checklist. Analisis data menggunakan statistik deskriptif untuk menghitung mean,median, modus. Pengkategorian dilakukan pada setiap subvariabel menggunakan teori Paretto. Hasil dari penelitian variabel input pada ketersediaan SDM tergolong kurang baik, ketersediaan sarana tergolong kurang baik, ketersediaan prasarana tergolong baik, dan ketersediaan form-form tergolong baik. Hasil penelitian variabel proses pada konseling pra-testing tergolong kurang baik dan konseling pasca-testingtergolong kurang baik. Hasil penelitian variabel output pada pelayanan dukungan berkelanjutan tergolong kurang baik.Kata Kunci :Implementasi, Layanan VCT, HIV/AIDS